STRATEGIES FOR PROMOTING ENTREPRENEURSHIP SKILLS ACQUISITION AMONG TECHNOLOGY AND VOCATIONAL EDUCATION STUDENTS FOR SELF-EMPLOYMENT IN EBONYI AND ENUGU STATE - Onogu, Sunday Godstime (Top Educational Review Journal (TERJ), 2023)
The study was designed to determine the strategies for promoting entrepreneurship skill acquisition among Technology and Vocational Education (TVE) students for self-employment in Ebonyi and Enugu State Universities. Two research questions guided the study. The study adopted a survey research design. The population for the study was 55 TVE lecturers. Due to the manageable size of the population the entire population was used. The questionnaire was tested for reliability using Cronbach Alpha. The instrument for the study was 19 item questionnaire which were developed by the researchers. The research questions were answered using mean and standard deviation. It was found that institutional and governmental strategies promote entrepreneurial education among TVE students in Enugu and Ebonyi States. Based on the findings, the researchers recommended that: government should make policies that will promote entrepreneurship education. Facilities needed for entrepreneurship education should be made available by the institution